Training effects of short bouts of stair climbing on cardiorespiratory fitness, blood lipids, and homocysteine in sedentary young women. Issue 9 (23rd August 2005) - Boreham, C A G; Kennedy, R A; Murphy, M H; Tully, M; Wallace, W F M; Young, I
Abstract : Objectives: To study the training effects of eight weeks of stair climbing on Vo 2 max, blood lipids, and homocysteine in sedentary, but otherwise healthy young women. Methods: Fifteen women (mean (SD) age 18.8 (0.7) years) were randomly assigned to control (n = 7) or stair climbing (n = 8) groups. Stair climbing was progressively increased from one ascent a day in week 1 to five ascents a day in weeks 7 and 8. Training took place five days a week on a public access staircase (199 steps), at a stepping rate of 90 steps a minute. Each ascent took about two minutes to complete. Subjects agreed not to change their diet or lifestyle over the experimental period. Results: Relative to controls, the stair climbing group displayed a 17.1% increase in Vo 2 max and a 7.7% reduction in low density lipoprotein cholesterol (p<0.05) over the training period. No change occurred in total cholesterol, high density lipoprotein cholesterol, triglycerides, or homocysteine. Conclusions: The study confirms that accumulating short bouts of stair climbing activity throughout the day can favourably alter important cardiovascular risk factors in previously sedentary young women. Such exercise may be easily incorporated into the working day and therefore should be promoted by public health guidelines.